Unemployment compensation in the United States: Provisions and institutional changes since the 1980s - Britta Grell (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
Systems of unemployment compensation in many OECD countries have undergone major institutional changes during the past three decades. These changes were a response to severe fiscal pressures and the fear of potential adverse effects on labor market behaviour that might arise from generous public income support. This is less true for the United States where the basic structure of the safety net for unemployed workers has only experienced modest modifications since the 1980s. The paper gives an overview of the most important legal reforms and the current provisions at the state and federal level available to unemployed workers and their families, including unemployment insurance and means-tested public assistance programs (Food Stamps, housing assistance, etc.). It concludes that the decentralized unemployment insurance system in the United States contains a major gap between the statutory coverage of workers and the proportion of unemployed actually claiming and receiving benefits.
Keywords: 330; Arbeitslosenversicherung; Reform; Arbeitslosigkeit; USA